Victory at yorktown eaudiobook - Gingrich, Newt (George Washington, 2012)
New York Times bestselling authors Newt Gingrich and William R. Forstchen pen the triumphant conclusion to their George Washington series-a novel of leadership, brotherhood, loyalty, and the victory of the American Revolutionary cause. 1781. After three years in a bitter stalemate, General Washington decides to embark on one of the most audacious moves in American military history. He will take nearly his entire army out of New Jersey and New York and force march it more than three hundred miles in complete secrecy. He must pray that the French navy is successful in blockading Chesapeake Bay, so that he can fall upon British General Cornwallis at Yorktown. It is a campaign laden with "Ifs" but the deadlock must be broken, otherwise the American spirit, after six long years of war, will crumble. A tour de force narrative of one of America's most important heroes, Victory at Yorktown vividly portrays Washington's unparalleled courage, determination, and patriotism as he leads his professional army, once a "rabble in arms," to the heat of the Battle of Yorktown to execute the Revolution's most decisive contest.